THE IMPLEMENTATION OF INVENTORY ACCOUNTING INFORMATION SYSTEMS: A SYSTEMATIC LITERATURE REVIEW - Ria; Khairul Saleh L. Tobing; Dhieka Avrilia Lantana; Kumba Digdowiseiso; Nurasyikin Jamaludin (Journal of Accounting Research, Utility Finance and Digital Assets, 2023)
The significance of efficiency and accuracy in inventory management is crucial for achieving operational success and making informed decisions. The objective of this study is to examine and evaluate the utilization of inventory accounting information systems in different organizations. This study employs the Systematic Literature Review (SLR) method to gather, assess, and integrate findings from diverse and pertinent literature sources. The findings of this study demonstrate that the adoption of an inventory accounting information system yields substantial advantages, such as enhanced operational effectiveness, decreased storage expenses, improved precision of financial statements, and simplified monitoring and analysis of inventory data. The discussion emphasizes the significance of choosing a suitable platform, providing employee training, and ensuring seamless integration with current business processes. This research demonstrates that investing in the implementation of an inventory accounting information system is a prudent measure to enhance operational efficiency, facilitate well-informed decision-making, and sustain competitiveness in a progressively competitive market.